Nontuberculous mycobacterial pulmonary disease incidence among elderly patients with bronchiectasis. Issue 6 (23rd June 2022) - Schildknecht, Kimberly; Winthrop, Kevin L.; Prevots, D. Rebecca; Blakney, Rebekah; Henkle, Emily
Nontuberculous mycobacteria (NTM) are environmental pathogens causing disease in humans; however, not everyone exposed develops disease [1]. Those with underlying pulmonary diseases, persons over 60 years old and women have an increased risk for nontuberculous mycobacterial pulmonary disease (NTM-PD) [1, 2]. Bronchiectasis is a lung condition characterised by chronic airway dilation and inflammation, resulting in impaired mucus clearance, and is associated with NTM-PD [1–3]. Both NTM-PD and bronchiectasis are increasing in incidence in the USA [2, 3]. Although patients with bronchiectasis are at increased risk of acquiring NTM-PD [1, 2], the incidence of NTM-PD in these patients is not well described. Previous US Medicare data estimated those with bronchiectasis were 50- to 75-fold more likely to have a diagnosis of NTM-PD than those without bronchiectasis [4]. The objective of this analysis was to estimate the incidence of NTM-PD among US Medicare enrolees newly diagnosed with bronchiectasis over the age of 65 years. Incidence of NTM-PD was estimated among US Medicare beneficiaries newly diagnosed with bronchiectasis between 2006 and 2014. Overall incidence of NTM-PD was found to be as high as 1950 per 100 000 person-years. https://bit.ly/3iAr4o5